A Survey on Malware Detection and Analysis - Smallman, Joshua (Journal of Science & Technology, 2024)
Malware, or malicious software, poses a significant threat to the security and functionality of computer systems globally. This survey provides a comprehensive analysis of current malware detection and analysis methods, focusing on data mining methodologies. The study categorizes malware detection techniques into signature-based and behaviour-based approaches, highlighting their respective strengths and weaknesses. It explores heuristic techniques enhanced by artificial intelligence, including neural networks and genetic algorithms, to improve detection accuracy. The literature review examines host-based and network-based intrusion detection systems, hybrid systems, and virtual machine introspection. The paper also discusses static and dynamic analysis methods, emphasizing the importance of analysing malware in controlled environments. Through detailed examination, this survey aims to present a thorough understanding of contemporary malware detection strategies and their applications, offering insights for future advancements in the field.
Keywords: Malware; Malware Detection; Data Mining; Signature-Based Detection; Behaviour-Based Detection; Artificial Intelligence; Intrusion Detection Systems; Static Analysis; Dynamic Analysis; Virtual Machine Introspection